Novel indole-2-carboxylic acid analogues: Synthesis and a new light in to their antioxidant potentials - Naik, Nagaraja; Sharath, Vishwanath; Kumar, Honnaiah Vijay (European Journal of Chemistry, 2012)
Two series of novel indole-2-carboxylic acid derivatives is reported. In the first series, N-substituted derivatives (3a-h) were synthesized via acylation of indole-2-carboxylic acid followed by aldol condensation reaction. Whereas, in the second series, indole-2-carboxamides (5a-g) were synthesized through conversion of acid to its acid chloride followed by coupling of substituted anilines. Structures of the newly synthesized compounds were confirmed by elemental analysis and spectral IR, 1H NMR and mass data and were screened for antioxidant activity. Among the first series, compound 3g showed higher antioxidant activity and whereas, in the second series compounds 5b and 5c exhibited potential antioxidant activity. Compounds 3g, 5b and 5c exhibited for its enhanced antioxidant activity.